Medical management of pulmonary disease caused by Mycobacterium avium complex - Iseman, Michael D (Clinics in chest medicine, 2002)
The current medical therapy for Mycobacterium avium complex is controversial. American Thoracic Society recommendations advocate empiric therapy with drug susceptibility testing only for clarithromycin. At National Jewish, where we mainly see cases complicated by treatment failure and drug intolerance, we use in vitro susceptibility testing and therapeutic drug monitoring to optimize efficacy and reduce toxicity.